Penerapan Metode PDM dan Pert pada Proyek Pembangunan Pusat Layanan Haji dan Umroh Terpadu Kota Balikpapan - Azan Yamani Purwanto; Gunaedy Utomo; Reno Pratiwi (Jurnal Talenta Sipil, 2026)
The construction of the Integrated Hajj and Umrah Service Center (PLHUT) in Balikpapan City is a construction project that requires effective time management to ensure timely completion. This study aims to analyze the critical path and the probability of successful project completion using the Precedence Diagram Method (PDM) and Program Evaluation and Review Technique (PERT). The PDM method is utilized to identify the project’s critical path by structuring the interdependencies of work items, visualized through a network diagram. Meanwhile, the PERT method is employed to calculate the probability of project completion within the planned duration, taking into account the uncertainties in activity durations. Based on the analysis results, the PLHUT construction project in Balikpapan City, with a planned duration of 160 days, contains several critical activities that require careful resource management and scheduling. The probability calculation using the PERT method indicates a high likelihood of completing the project on time. Thus, the combination of PDM and PERT methods serves as an effective approach in construction project management to enhance efficiency and schedule accuracy.